Hubungan Dukungan Keluarga, Kualitas Tidur, Stres Akademik dengan Gangguan Kecemasan pada Siswa SMAN 1 Sumbawa Besar - Dema Ratu Zulfiah; Aena Mardiah; Yolly Dahlia; Ronanarasafa Ronanarasafa (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Anxiety disorders are common mental health problems among adolescents, particularly high school students who face academic demands, social pressure, and emotional changes. Family support, sleep quality, and academic stress are considered factors related to students’ anxiety levels. This study aimed to examine the relationship between family support, sleep quality, academic stress, and anxiety disorders among students of SMAN 1 Sumbawa Besar. An analytical study with a cross-sectional design was conducted involving 114 students selected through stratified random sampling. Data were collected using the Perceived Social Support–Family (PSS-Fa), Pittsburgh Sleep Quality Index (PSQI), Educational Stress Scale for Adolescence (ESSA), and Depression Anxiety Stress Scale (DASS-42). Bivariate analysis was performed using the chi-square test, while multivariate analysis employed binary logistic regression. Bivariate results indicated significant associations between family support, sleep quality, academic stress, and anxiety disorders (p < 0.05). However, multivariate analysis revealed that only family support and sleep quality were significantly associated with anxiety disorders, while academic stress was not significant after controlling for other variables. These findings suggest that anxiety prevention efforts should prioritize strengthening family support and improving sleep quality, alongside academic stress management within the school environment.